Epistemological Obstacle Siswa dalam Menyelesaikan Soal pada Pokok Bahasan Persamaan Kuadrat - Marlinda, Sheli; Effendi, Kiki Nia Sania (Radian Journal: Research and Review in Mathematics Education, 2023)
Epistemological obstacles arise due to the limited knowledge possessed by students in certain contexts so when facing different contexts, students will experience obstacles in finding a relationship and conceptual linkage. This study aims to describe students' epistemological obstacles in solving problems on the subject of quadratic equations. The approach used in this study is a qualitative approach with a descriptive method. Data collection was obtained by giving a written test of three quadratic equation questions adopted from previous studies and conducting unstructured interviews. The subjects studied were all ninth-grade students of SMP Negeri 2 Majalaya, Karawang, and using probability random sampling techniques, a sample of 44 students was taken. The test data were then processed and grouped into three categories, namely high, medium, and low. Then the students' answers were analyzed and reviewed from the epistemological obstacle indicators. Then the researcher conducted unstructured interviews to find out more about the obstacles that occurred to the three selected participants. The results of the study showed that the epistemological obstacles experienced by students in solving problems on the subject of quadratic equations were: (a) conceptual obstacles, there were participant errors in determining definitions and not writing formulas in a given problem; (b) procedural obstacle, there are participants who have not been able to solve the problem according to the requested procedure; and (c) operational technique obstacle, there are participants who have errors in calculations in the process of working on certain steps and errors in writing formulas, the process of working, and the final results in solving the problem. It is hoped that the findings in this study can have a significant impact on the mathematics learning process, both theoretically and applicatively.